Effect of conjugation and aromaticity of 3,6 di-substituted carbazoles on triplet energy and the implication of triplet energy in multiple-cyclic aromatic compounds - Woon, Kai Lin; Ariffin, Azhar; Ho, Kar Wei; Chen, Show An (Royal Society of Chemistry, 2018)
It is well-known that short conjugation is needed to obtain a high triplet energy. Carbazole has 3 fused rings and yet it has a high triplet energy. In order to illuminate the reason behind this, we synthesized a range of carbazole derivatives with substitution at the 3,6-positions. All carbazoles with phenyl moieties substituted at the 3,6-positions exhibit a lower triplet energy than that of carbazole itself. We also quantified the aromaticity of carbazole using the nucleus-independent chemical shift tensor. We discovered that the five-membered heterocyclic aromatic ring in carbazole has reduced aromaticity. This results in a reduced conjugation effect between the five-membered heterocyclic aromatic ring and the neighboring benzene rings. Inspired by this finding, the triplet energies of compounds with up to seven benzene units separated by heterocycles (furan, pyrrole, thiophene, silole, and phosphole) and cyclopentadiene were calculated using time-dependent density functional theory. A high triplet energy (>3 eV) can be obtained by alternating high aromaticity and reduced aromaticity in highly extended fused π systems containing furan and pyrrole. In tricyclic aromatic compounds (dibenzofuran, carbazole, fluorene, dibenzothiophene, 5H-benzo[b]phosphinedole and 9H-9-silafluorene) and their extended fused π systems that we have examined so far, the triplet energy is related to the electronegativity of the oxygen, nitrogen, carbon, sulfur, phosphorous and silicon atoms. These findings provide new intuitive insight related to the structures of molecules and the triplet energies, which could be useful in organic optoelectronics.